El maltrato intrafamiliar y su impacto en el desarrollo escolar de los niños y niñas del comedor de apoyo escolar CAE del albergue Padre Julio Villarroel Ocaña de la ciudad de Loja. - Caraguay Guiallas, Nancy Beatriz (2013)
The family is the cornerstone of society, this is where they are born, learn, educate, and acquire knowledge, principles, rules for living together in harmony. The family members assures his emotional stability, social and economic when it breaks any of them is when there is domestic abuse. While domestic abuse is one of the social problems afliguen to most of Ecuadorian families, which affects not only women who are subjected to it but their sons and daughters in the personality development during different evolutionary stages that human beings have. The presentation and discussion of results emphasizes the data obtained in the investigation of the field where we let entreveer that parents do not have a good relationship with your children what determines students (as) of the Hall School Support (CAE), reciven abuse by family members harming school performance, and problems arise in the development of his personality this confirms that children (as) the hostel demonstrate aggressive behavior, arrogant, disobedient to their teachers, peers affecting their development and concentration during class. It can be concluded that domestic abuse drastically influences on school performance and emotional development of children (as) of School Support CAE, Dining hence the family plays a very important role because it must provide its members love, understanding and safety standards emphasizing social and family life.